(untitled) (Global Journal of Science Frontier Research, 2021)
To fulfil country’s irrigation and power requirements various large capacity dams have been constructed on major rivers in last 50 years. The long term sustainability of these structures is largely dependent on hydro-environment and the capacity of these structures to resist weathering action, chemical attack, abrasion, or any other process of deterioration. The concrete deterioration is directly influenced by various geographical, climatic and ecological conditions. The chemical reactions between cement and water enable the setting and hardening of cement, resulting in a binding medium for the aggregates and development of strength. Quality of water plays an important role in the production of concrete. There are some chemical environments under which the useful life of even the best concrete will be affected adversely. The aggressiveness of water is dependent on the pH value, the total dissolved salts, the degree of hardness, soluble chlorides, sulphates, carbonation, temperature and alkalinity etc. Understanding these conditions permit measures to be taken to prevent or reduce deterioration.